The right to an age-friendly city : redistribution, recognition, and senior citizen rights in urban spaces - Joy, Meghan, 1983- (McGill-Queen's studies in urban governance, 2020)
"A context of aging populations and urbanization has sparked a global movement to make urban spaces age-friendly. The Age-Friendly City program, developed by the World Health Organization, aims to improve local environments for all population groups, promote a positive aging identity, and empower local policy actors to support senior citizens. Despite growing enthusiasm and policy work by local governments worldwide, considerable gaps remain. These lacunae have led scholars and activists alike to align age-friendly city work with the concept of the right to the city. In The Right to an Age-Friendly City Meghan Joy zeroes in on the intricacies of developing an environment that promotes social and spatial justice for the elderly in Toronto. Weaving together the stories, struggles, and victories of local activists, government staff, and frontline service providers, Joy maps this complex policy area and examines the ways in which age-friendly work successfully enhances senior citizens' access to services and support in the local environment, recognizes the diverse needs of senior citizens in the city, and empowers policy actors from local government and the non-profit sector to support senior citizens. A detailed and timely examination, The Right to an Age-friendly City offers both broad and tangible insights into the intermingled political, economic, cultural, and administrative changes needed to protect the rights of senior citizens to access urban space in Toronto and beyond."--